2017
DOI: 10.1080/08912963.2016.1265956
|View full text |Cite
|
Sign up to set email alerts
|

Bivalve borings in Lower JurassicLithiotisfauna from northeastern Italy and its palaeoecological interpretation

Abstract: Random shell sections of the Pliensbachian (Early Jurassic) larger bivalve Opisoma from columns within the Main Post Office building of Ferrara, northern Italy, have been discovered to bear neat clavate-shape boreholes. These boreholes belong to the ichnogenus Gastrochaenolites Leymerie and represent bivalve borings. Opisoma is a subordinate component of the Lithiotis fauna characterised by aberrant shells thriving in tropical lagoonal settings which were widespread throughout the Tethyan and Panthalassa coast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
4
0
1
Order By: Relevance
“…This suggests that (1) sedimentation rates were high enough to hamper encrusting epifauna and bioeroding endofauna and (2) parautochthonous to allochthonous lithiotid shells, which could have been exposed for longer, to show increased encrustation and bio-erosion. The only detailed study on the occurrence of bioerosion in a member of the lithiotid fauna suggested seasonal or temporal mesotrophic conditions within an overall oligotrophic regime as a factors for this rare occurrence in Pliensbachian larger bivalves (Bassi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that (1) sedimentation rates were high enough to hamper encrusting epifauna and bioeroding endofauna and (2) parautochthonous to allochthonous lithiotid shells, which could have been exposed for longer, to show increased encrustation and bio-erosion. The only detailed study on the occurrence of bioerosion in a member of the lithiotid fauna suggested seasonal or temporal mesotrophic conditions within an overall oligotrophic regime as a factors for this rare occurrence in Pliensbachian larger bivalves (Bassi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The Mesozoic cementers predominantly inhabited shallow water environments, where some gregarious forms (e.g., lithiotids, rudists, oysters) originated highly dense aggregates (bivalve mounds, reefs, pavements, carpets), influencing the sedimentation rates and carbonate platform dynamics (e.g., F眉rsich et al, 1994;Gili et al, 1995;Riding, 2002;Fraser et al, 2004;Skelton and Gili, 2012;Harper, 2012;Posenato and Masetti, 2012;Bassi et al, 2017). Despite the high abundance, widespread geographic diffusion and long-time ranging distribution, little is known about the functional morphology of the shell, taphonomy and geometries of the Chondrodonta accumulations.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Drill holes in fossil shells and other hard substrates from the Lower Jurassic may have had different origins and served different purposes. For example, domichnia were previously reported from the Lower Jurassic, made by bivalves on epifaunal bivalves ( Gastrochaenolites ; Bassi et al 2017) and by acrothoracid barnacles on hard substrates ( Rogerella ) from the Amaltheenton Formation (Keupp and Schweigert 2021). The drill-hole characteristics in the studied specimens鈥攖he shape of the drill holes ( Oichnus paraboloides ), the presence of boreholes on shells of infaunal taxa, and the concentration of holes on certain sites (site selectivity)鈥攄o not support their interpretation as domichnia.…”
Section: Discussionmentioning
confidence: 99%